ICT and agriculture in India - Balasubramanian Dhandapani; Rico Lie; Pierre Grard (Netcom)
Information and Communication Technologies (ICTs) have contributed in one way or the other to many transformations in contemporary society. The contexts and the impacts of such transformations are particularly significant for developing societies like India. The relevance of new computing technologies and their effective implementation in developing countries is widely debated, both at policy and community level. Needless to say, FOSS (Free Open Source Software) has encouraged the participation of civil society, creating potential for developing specific information technology tools. In this context, the OSCAR-project (Open Source Simple Computer for Agriculture in Rural Areas) is an initiative from European and South Asian Institutions to assist decision making in agriculture. OSCAR developed a weed identification system for the major weed species in rice-wheat cropping systems of the Indo-Gangetic Plains (IGPs) covering Pakistan, India, Nepal and Bangladesh. An integral part of the OSCAR-project is its applicability to three categories of potential users: farmers, extension officers, and, scientists and students in agricultural sciences. OSCAR was evaluated through extensive interactions with farmer groups, extension personnel, IT specialists, NGO and UN staff, government officials, scientific researchers and PhD students in various disciplines and MSc students from various programs in all the four IGP countries. The experience from OSCAR is helpful in understanding the larger contexts and the impact of ICT interventions in an interdisciplinary framework.